The Value of a Finance Journal Publication - Swidler, Steve; Goldreyer, Elizabeth (Journal of Finance, 1998)
The empirical analysis examines the salary and publication records of 311 finance professors at public research universities to calculate the worth of a top finance journal article. Within rank, salary regressions provide measures of the direct returns of a journal publication, while probit models consider the indirect returns that result from promotion. Ultimately, the analysis uses a reduced form salary equation to measure both the direct and indirect effects of publishing a journal article. Depending on professorial rank, the present value of the first top finance journal article is between extbackslash19,493 and extbackslash33,754, with the additional result of large returns to subsequent publications.